Adaptation to Climate Change: Barriers in the Turkish Local Context - Balaban, Osman; Şenol Balaban, Meltem (TeMA - Journal of Land Use, Mobility and Environment, 2015)
Climate change is one of the greatest environmental challenges that we face today. A certain level of climate change is now unavoidable. Along with mitigation efforts to curb further global warming, we have to take actions to adapt to the changing climatic conditions. Cities are on the front lines of climate change impacts. Therefore, the role of cities in climate change adaptation has been widely acknowledged in the last two decades. There are various obstacles that prevent city governments to develop adaptation policies. While some of these obstacles are universal, some of them are context-specific. Based on the review of key policy documents and interviews with public officials, this paper focuses on analyzing the main barriers that prevent Turkish cities to develop and implement effective adaptation policies. The research results indicate that cities in Turkey face very similar barriers with their international counterparts in adaptation policymaking. Among the main barriers in the Turkish local context are lack of institutional and technical capacity as well as awareness and coordination problems among actors of climate policy. Due to such barriers, “municipal voluntarism”, which mostly leads to voluntary and spontaneous actions, is the prevailing approach to climate policy development in Turkish cities. A series of reforms should be enacted by the central government to help cities overcome the barriers to climate change adaptation.